ضَبْطُ الْهَمْزَةِ الْمُسَهَّلَةِ وَحَالَاتُهَا - ذهبي بوبكر الصديق; بوغزالة عبد الكريم (University of Eloued جامعة الوادي, 2023)
باب الهمز في علم الضّبط القرآنيّ أطولُ الأبواب وأصعبُها، ومن سُبُل تذليله التّدقيقُ في فرعٍ من فروعه، ومن هذه الفروع ما تقدّمُهُ هذه الدّراسة التي هي "ضَبْطُ الْهَمْزَةِ الْمُسَهَّلَةِ وَحَالَاتُهَا" وتهدِف إلى التّعرّف على ضبط الهمز المسهّل: من حيثُ الهيئةُ واللّونُ والموضعُ؛ وكذلك معرفة جميع حالات ضبط الهمزة المسهّلة: في كلمة، وفي كلمتين؛ عند انفرادها، وعند اجتماعها مع واحدة، وعند اجتماعها مع اثنتَيْنِ. وإنّ من أهمّ النتائج: أنَّ الهمزة المسهّلة في المصحف تُضبَطُ إمّا نقطةً حمراءَ، وإمّا رأْسَ عيْنٍ حمراءَ؛ وأنها إمّا ألّا تكون لها صورة فتُجعل على السّطر، أو تُلحق صورتُهَا بالحمراء: ألفًا أو ياءً، أو واوًا؛ وإمّا أن تكون لها صورة في الرّسم: ألفًا أو ياءً أو واوًا. Abstract: The chapter of Al-Hamz in the Quranic vowelization is the longest and the most difficult. One of the ways to overcome it is to scrutinize one of its branches. Among these branches is what this study provides, which is “Adjust the Light Hamza and its Cases” and aims to identify the vowelization of the light hamza: In terms of shape, color and position; as well as the cases of the vowelization of the light hamza: in one word, and in two words; when alone, when meeting with one, and when meeting with two. One of the most important results: that the light hamza in the Quran is vowelized either with a red dot or the head of a red ‘eyn’; and that it either does not have a writing, so it is placed on the line or its writing is appended to an ‘aliph’, a ‘yaa’ or a ‘waw’ red; either it has a writing in Quran writing: an ‘aliph’, a ‘yaa’, or a ‘waw’.
Keywords: الهمزة; التسهيل; الضبط; مواضع; صورة